Corrosion behaviour of mild steel in chloride solutions with Na2HPO4 additive and the development of antifreeze. (13th March 2018) - Wang, Rongguang; Nagano, Hiroo; Ling, Yunhan
ABSTRACT: Chloride salts can prevent roads from freezing in cold regions, together with severe corrosion on steel constructions. To develop an ecological and low-corrosive antifreeze, di-sodium hydrogenphosphate (Na2 HPO4 ) was chosen as the additive into chloride salts. The addition of Na2 HPO4 into either of the antifreezes of natural salt (N/S), NaCl, CaCl2 or MgCl2 can suppress the corrosion reaction of mild steel in the 3.0% antifreeze solution. Moreover, the addition of CaCl2 or MgCl2 into the antifreeze containing NaCl and 2.0% Na2 HPO4 significantly decreased the corrosion rate. According to polarisation and XPS analyses, it is evident that the obtained low corrosion rates on mild steel are related to the suppressed cathodic and anodic reactions and the formation of a protective film containing Fe, P, O, Ca or Mg. This paper is part of a supplementary issue from the 17th Asia-Pacific Corrosion Control Conference (APCCC-17) .